2005
DOI: 10.1007/s00454-005-1159-1
|View full text |Cite
|
Sign up to set email alerts
|

Lower Bound for the Maximal Number of Facets of a 0/1 Polytope

Abstract: Let f n−1 (P) denote the number of facets of a polytope P in R n . We show that there exist 0/1 polytopes P with f n−1 (P) ≥ cn log 2 n n/2 , where c > 0 is an absolute constant. This improves earlier work of Bárány and Pór on a question of Fukuda and Ziegler.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 11 publications
0
12
0
Order By: Relevance
“…This is a consequence of the next lemma (which essentially appears in [7], [2] and [9]). Lemma 4.1: Let 0 < r < λ(α).…”
Section: Threshold For the Volumementioning
confidence: 85%
See 1 more Smart Citation
“…This is a consequence of the next lemma (which essentially appears in [7], [2] and [9]). Lemma 4.1: Let 0 < r < λ(α).…”
Section: Threshold For the Volumementioning
confidence: 85%
“…The method they introduced in [7] proved to be extremely useful and accurate; for example, it played a key role in the approach introduced by Bárány and Pór in [2] in order to establish that there exist ±1 polytopes with a superexponential number of facets, which was further developed in [9] and [10].…”
Section: Introductionmentioning
confidence: 98%
“…In particular, if the 2 d vertices of the entire cube are ordered lexicographically then the total number of facets of all intermediate polytopes produced by an incremental convex hull algorithm to compute the cube is bounded from above by 3d · 2 d , while for an arbitrary (even for a random) ordering there might be intermediate polytopes with super-exponentially many vertices (due to the results of Bárány and Pór [2] and Gatzouras et al [5]). …”
Section: Incremental Convex-hull Algorithmsmentioning
confidence: 97%
“…They showed that a random d-dimensional 0/1-polytope with roughly 2 d/log 2 d vertices in expectation has at least (roughly) 2 (1/4)d log 2 d facets. Recently, this bound was even improved to 2 (1/2)d log 2 d by Gatzouras et al [5]. The best known upper bound currently is O((d − 2)!)…”
Section: Introductionmentioning
confidence: 94%
“…[4,8,14], see also the survey [9]). Random polytopes (including +1/−1 polytopes) also play a very important role in combinatorics; we mention only a few recent results [1][2][3].…”
Section: Introductionmentioning
confidence: 99%